THE CONCEPT OF COMMUNITY EMPOWERMENT: THE PROPHET MUHAMMAD'S PERSPECTIVE (International Conference on Social and Islamic Studies, 2022)
In the developing and developed countries, poverty has become a big problem that must be resolved immediately. Poverty can cause social inequality. The Prophet Muhammad even explained that poverty is very close to disbelief. One of the instruments that can be used to overcome the problem of poverty is to do empowerment. In fact, there are many verses in the Qur'an that discuss empowerment. Empowerment is carried out as an effort in community development which aims to build initiatives from the community in carrying out their social activities to improve the conditions and situations that exist in themselves. This becomes interesting to discuss in more depth because in practice, empowerment has been carried out by the Prophet Muhammad. So the purpose of this study is to describe how the concept of community empowerment carried out by the Prophet Muhammad. This research method uses a qualitative approach to the type of library research. The data used is primary obtained from several journals and books. The data analysis technique uses descriptive, in which the researcher describes the concept of community empowerment by exploring Islamic empowerment values ​​in the life of the Prophet Muhammad. The concept of empowering the Prophet's perspective emphasizes the principles of justice (al-Dari), the principle of equality (al-musawah), brotherhood (al-ikha), the principle of mutual help (al-ta'awun), the principle of participation and the principle of work ethic. While the strategic steps taken by the Prophet in empowering the community were first to form and develop independent community individuals, secondly to distribute wealth fairly and evenly, thirdly to build education and guidance and fourthly to prevent market distortions. The Prophet paid great attention to empowering his people. The empowerment that is carried out still adheres to Islamic values ​​because in fact the goal of welfare to be achieved is not only in this world but in the hereafter.